Avaliação e valorização do patrimônio jesuítico em Uruguaiana/RS - Morari, Mariana Nicorena (2023)
The territory belonging to the county of Uruguaiana was part of the old Jesuit resort of Yapeyú. The structures left by the resort and the cattle introduced to this location by the Jesuit priests shaped the ways of doing and living in the region through the cultural landscape left behind, forming the identity of the Uruguaianense population. The research aimed to evaluate the local landscape, promoting the recognition and appreciation of the Jesuit cultural landscape through its material and immaterial heritage. The methodology began with the characterization of the county of Uruguaiana and the subsequent delimitation of the study areas based on the visual ranges of the sites, followed by technical analyses of the study sections using geoprocessing. The research also included the application of questionnaires in digital format to assess the landscape with popular participation and also a multidisciplinary assessment of the landscape with the participation of specialists from the different areas that work in the landscape. In the end, management, preservation, and conservation guidelines for the landscape were developed, taking into account the current situation, trying to alleviate current problems and value the positive aspects, protecting the unique identity of the region and transmitting its legacy to future generations.